The Application of Reality Therapy with the WDEP Technique to Improve the Self-Esteem of People Living with HIV/AIDS at Panti Bina Insan Bangun 2 Jakarta - Farita Djakiman, Lun; Andini, Shinta; Cholidah, Nur; Sovitriana, Rilla (International Journal of Social Science, Education, Communication and Economics, 2025)
This study explores the application of Reality Therapy using the WDEP (Wants, Doing, Evaluation, Planning) technique to improve self-esteem among People Living With HIV/AIDS (PLWHA) at the Panti Sosial Bina Insan Bangun Daya II in East Jakarta. As PLWHA often face stigma, rejection, and psychological distress, self-esteem becomes a crucial component for mental resilience and social reintegration. This quasi-experimental research employed a pre-test and post-test control group design, involving five selected participants diagnosed with HIV/AIDS aged 18 and above. The intervention consisted of ten group counseling sessions focusing on helping participants identify their goals, assess current behaviors, and plan realistic strategies for change. Self-esteem levels were measured using the Coopersmith Self-Esteem Inventory (CSEI). Pre-test results indicated low levels of self-esteem, with an average score of 31. Following the intervention, the post-test average rose to 48, signifying a 54% improvement and placing participants in the high self-esteem category. Qualitative observations during therapy sessions revealed significant behavioral transformations, including increased emotional regulation, social interaction, self-acceptance, responsibility, and future orientation. The findings demonstrate that Reality Therapy with WDEP is an effective, culturally adaptable approach to psychological rehabilitation in institutional settings. It not only enhances self-esteem but also empowers PLWHA to rebuild their sense of self-worth, establish supportive relationships, and envision a hopeful future. The study contributes to expanding evidence-based psychosocial interventions for marginalized populations in Indonesia.